Insights into the repression of fibroin modulator binding protein-1 on the transcription of fibroin H-chain during molting in Bombyx mori. (January 2019) - Liu, Lina; Wang, Yejing; Li, Yu; Guo, Pengchao; Liu, Chun; Li, Zhiqing; Wang, Feng; Zhao, Ping; Xia, Qingyou; He, Huawei
Abstract: Fibroin modulator binding protein-1 (FMBP-1) is a novel DNA-binding protein containing a conserved score and three amino acid peptide repeat (STPR) domain. The roles of factors containing STPR domain are less known. Although multiple transcription factors are involved in the transcriptional regulation of silk protein genes during the development of silkworm, the mechanism of transcriptional repression of silk protein genes during molting remains unclear. Here, we found that FMBP-1 expression was contrary to that of fibroin heavy chain ( fib-H ) during the fourth molting period of Bombyx mori . FMBP-1 repressed fib-H promoter activity by directly binding to the −130 element in the fib-H promoter region. We also identified two proteins, Bmsage and Bmdimm, that interacted with FMBP-1 in the posterior silk gland of silkworm larvae, and further verified these interactions by far western blotting and microscale thermophoresis in vitro, as well as co-immunoprecipitation and bimolecular fluorescence complementation at the cellular level. The luciferase reporter assay showed that the interaction between FMBP-1 and Bmdimm antagonized the activation of Bmdimm on fib-H transcription, but did not affect FMBP-1-mediated transcriptional repression on fib-H gene. Therefore, we proposed the following mechanism of fib-H transcriptional repression by FMBP-1 during the molting of silkworm larvae: 1) FMBP-1 directly binds to the −130 element in the fib-H promoter to repress fib-H transcription; 2) FMBP-1 interacts with Bmdimm to antagonize the activation of Bmdimm on fib-H transcription. Our findings promote a better understanding of fib-H transcriptional regulation and provide novel insights into the transcriptional repression of fib-H by FMBP-1 and basic helix-loop-helix factors Bmdimm during the molting of silkworm larvae. Our study also provides valuable information regarding the biological function of factors containing STPR domain. Graphical abstract: Image 1 Highlights: FMBP-1 represses fib-H gene transcription during molting of silkworm larvae. FMBP-1 directly binds to the −130 element upstream of fib-H promoter to repress fib-H transcription. FMBP-1 interacts with Bmdimm to antagonize the activation of Bmdimm on fib-H transcription.